Experimental Testing of Nonredundant Near-Field to Far-Field Transformations with Spherical Scanning Using Flexible Modellings for Nonvolumetric Antennas - Francesco D'Agostino; Flaminio Ferrara; Claudio Gennarelli; Rocco Guerriero; Massimo Migliozzi (International Journal of Antennas and Propagation)
This paper deals with the experimental testing of effective probe compensated near-field-far-field (NF-FF) transformations with spherical scanning requiring a minimum number of NF data. They rely on nonredundant sampling representations of the voltage measured by the probe, based on very flexible source modellings suitable for nonvolumetric antennas characterized by two dimensions very different from the other one. In particular, a cylinder ended in two half-spheres is adopted for modelling long antennas, whereas the quasi-planar ones are considered as enclosed in a rotational surface formed by two circular “bowls” having the same aperture diameter, but eventually different bending radii. The NF data needed to perform the classical spherical NF-FF transformation are then accurately and efficiently retrieved from the acquired nonredundant ones via optimal sampling interpolation formulas. A remarkable reduction of the number of the required NF data and, as a consequence, a significant measurement time saving can be so obtained. The experimental tests have been carried out at Antenna Characterization Lab of the University of Salerno and both the NF and FF reconstructions are resulted to be very good, thus confirming the accuracy and reliability of these NF-FF transformations from the experimental viewpoint too.